Contemporary rewritings of liminal women : echoes of the past - Borham Puyal, Miriam (New York : Routledge, 2020)
This book explores the concept of liminality in the representation of women in eighteenth and nineteenth century literature, as well as in contemporary rewritings, such as novels, films, television shows, videogames, and graphic novels. In particular, the volume focuses on vampires, prostitutes, quixotes, and detectives as examples of new women who inhabit the margins of society and populate its narratives. Therefore, it places together for the first time four important liminal identities, while it explores a relevant corpus that comprises four centuries and several countries. Its diachronic, transnational, and comparative approach emphasizes the representation across time and space of female sexuality, gender violence, and women's rights, also employing a liminal stance in its literary analysis: facing the past in order to understand the present. By underlining the dialogue between past and present this monograph contributes to contemporary debates on the representation of women and the construction of femininity as opposed to hegemonic masculinity, for it exposes the line of thought that has brought us to the present moment, hence, challenging assumed stereotypes and narratives. In addition, by using popular narratives and media, the present work highlights the value of literature, films, or alternative forms of storytelling to understand how women's place in society, their voice, and their presence have been and are still negotiated in spaces of visibility, agency, and power.
1. Introduction: Liminality, Feminocentric Narratives, and the Polytemporality of the New Woman Liminality and Feminocentric Narratives Polytemporal (Feminist) History and the Trace Liminal Women and Popular Narratives 2. Female Vampires: On the Threshold of Time, Space, and Gender F(r)iends on the Threshold: Let the Right One In M/Others and Survivors through Time: A Vampire Story and Byzantium Eternity, Liminal Space, and the Outsider: Only Lovers Left Alive Empowering Liminal Women: A Girl Walks Home Alone at Night 3. Good and Bad, Private and Public: Prostitution as Liminal Identity Between Monsters and Machines: Frankenhooker The Freedom of the Prostitute or the Silence of the Wife: Dangerous Beauty Neo-Victorian Rewritings: Class, Gender, and Commodities in Slammerkin Sex and Power from the Eighteenth Century to Television: Harlots 4. Between Madness and Rebellion: Rewriting the Female Quixote Coloring Reality with Romance: from Bridget Jones's Diary to Crazy Ex-Girlfriend Escaping a Harrowing (Patriarchal) Reality: Pan's Labyrinth and Sucker Punch Idealistic Individuals in a Fallen World: Amélie and The Bookshop 5. To Be and Not to Be: Female Detectives between Old and New Women Resurrecting Kate Warne: The Pinkertons and My Favorite Thing Is Monsters Sherlock's Sisters at the Turn of the Century: Houdini & Doyle and Phryne Fisher Invisible Women: Reclaiming the Spy in The Bletchley Circle Past in the Present, the Gothic in the Noir: Dolores Redondo's Baztan Trilogy
OCLC-licensed vendor bibliographic record.
Keywords: Women in literature; Liminality in literature; Literature, Modern -- 18th century -- History and criticism; Literature, Modern -- 19th century -- History and criticism; LITERARY COLLECTIONS / General; LITERARY CRITICISM / General